'If I leave home, who will take care of mum?' Intergenerational transmission of parental trauma through projective identification. Issue 2 (3rd July 2017) - Knight, Zelda G.
ABSTRACT: Using the construct of projective identification and integrating it with the body of literature on intergenerational transmission of unsymbolized parental trauma, I describe the case of an adult daughter that illustrates intergenerational transmission of unsymbolized parental trauma. It is suggested that the daughter has unconsciously identified with the disavowed feelings of anxiety projected into her by her mother. The daughter's projective identification of her mother's unresolved past traumas prevent her from leaving the parental home for the first time, despite being 35 years old. In turn, it is thought that the mother's unconscious grasping onto her daughter is an attempt to avoid the confrontation of her own unprocessed fears implanted into her by her own mother, thus linking three generations of disavowal. As a way of extending the exiting theory, it is proposed that when there are long-term and inexplicable experiences of anxiety that coalesces around the intergenerational transmission of parental trauma, the term ' intergenerational transmission of traumatic anxiety ' can be used to describe it.